Role of CD4+ T and CD8+ T Lymphocytes-Mediated Cellular Immunity in Pathogenesis of Chronic Obstructive Pulmonary Disease - Weilin Xue; Jianying Ma; Yue Li; Chunxia Xie (Journal of Immunology Research)
This work was to explore the changes of T lymphocyte subsets in peripheral blood of patients with acute exacerbation of chronic obstructive pulmonary disease (COPD) (AECOPD) and the role of cellular immunity mediated in the disease process. Eighty-six patients with AECOPD who visited Qingdao Hiser Medical Center from June 2020 to December 2021 and 30 healthy people (controls) who underwent health examination in the same period were selected. The differences of pulmonary function (PF), arterial blood gas (ABG), blood routine inflammatory indexes, T lymphocyte and T lymphocyte subsets were compared between the two groups, and the correlation between T lymphocyte subsets and each index was analyzed. There were clear differences in PF, ABG, and PB inflammation indexes between AECOPD patients and the controls (P <0.05). Compared with the controls, the CD4+ and CD4+/CD8+ ratio in PB of AECOPD group were obviously decreased, and the CD8+ level was clearly increased (P <0.05); Th1 of CD4+ cell subsets and Tc1 of CD8+ cell subsets were significantly increased, while Th2 of CD4+ cell subsets and Tc2 of CD8+ cell subsets were obviously decreased (P <0.05). However, CD4+ was significantly positively correlated with lung function indexes, and significantly negatively correlated with neutrophils/lymphocytes and high-sensitivity C-reactive protein (P <0.05) and significantly positively correlated with Hs-CRP (P <0.05). In summary, CD4+ and CD8+ T lymphocytes were involved in the occurrence and occurrence of AECOPD, the decrease of CD4+ and the increase of CD8+ may promote the deterioration of COPD.